Modeling the dynamics of neonatal CD8+ T‐cell responses. Issue 9 (31st May 2016) - Reynaldi, Arnold; Smith, Norah L; Schlub, Timothy E; Venturi, Vanessa; Rudd, Brian D; Davenport, Miles P
Abstract : Neonates are particularly susceptible to a number of infections, and the neonatal CD8 + T‐cell response demonstrates differences in both the phenotype and magnitude of responses to infection compared with adults. However, the underlying basis for these differences is unclear. We have used a mathematical modeling approach to analyze the dynamics of neonatal and adult CD8 + T‐cell responses following in vitro stimulation and in vivo infection, which allows us to dissect key cell‐intrinsic differences in expansion, differentiation and memory formation. We found that neonatal cells started dividing 8 h earlier and proliferated at a faster rate (0.077 vs 0.105 per day) than adult cells in vitro . In addition, neonatal cells also differentiated more rapidly, as measured by the loss in CD62L and Ly6C expression. We extended our mathematical modeling to analysis of neonatal and adult CD8 + T cells responding in vivo and demonstrated that neonatal cells divide more slowly than adult cells after day 4 post infection. However, neonatal cells differentiate more rapidly, upregulating more KLRG1 per division than adult cells (20% vs 5%). The dynamics of memory formation were also found to be different, with neonatal effector cells showing increased death (1.0 vs 2.45 per day). Comparison of the division of human cord blood and adult naive cells stimulated in vitro showed more division in cord blood‐derived cells, consistent with the observations in mice. This work highlights differences of the cell‐intrinsic division and differentiation program in neonatal CD8 + T cells.